Critical thinking skills : developing effective analysis and argument. - Cottrell, Stella (Palgrave study skills, 2011)
Ideal for students who are mystified by lecturer comments such as 'more analysis needed', this title takes the art of analysis and breaks it down into easy-to-understand blocks, with clear explanations, good examples, and plenty of activities to develop understanding at each stage.